2016
DOI: 10.1016/j.jss.2015.11.028
|View full text |Cite
|
Sign up to set email alerts
|

One-hour PTH after thyroidectomy predicts symptomatic hypocalcemia

Abstract: Background A major morbidity following total thyroidectomy is hypocalcemia. While many clinical factors and laboratory studies have been correlated with both biochemical and symptomatic hypocalcemia, the ideal use and timing of these tests the remains unclear. We hypothesize one-hour (PACU) PTH will identify patients at risk for symptomatic hypocalcemia. Methods This prospective study evaluated 196 patients undergoing total thyroidectomy. Serum calcium and PTH levels were measured one hour after surgery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Some surgeons routinely prescribe oral supplements, whereas others favor a selective approach using postoperative levels of serum calcium, PTH, or both. 9,21,22 These data suggest that more frequently prescribing oral supplementation is associated with decreased incidence of clinically severe hypocalcemia (ie, cases resulting in clinic or emergency department evaluations or readmission). A previous study 23 found that routine calcium and vitamin D supplementation is costeffective because it decreases health care resource use, whereas another study 21 argued that selective supplementation is equally cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons routinely prescribe oral supplements, whereas others favor a selective approach using postoperative levels of serum calcium, PTH, or both. 9,21,22 These data suggest that more frequently prescribing oral supplementation is associated with decreased incidence of clinically severe hypocalcemia (ie, cases resulting in clinic or emergency department evaluations or readmission). A previous study 23 found that routine calcium and vitamin D supplementation is costeffective because it decreases health care resource use, whereas another study 21 argued that selective supplementation is equally cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…A part from prevention, treatment of hypocalcemia is indicated in patients with symptoms, with a level of corrected calcium less than 7.5 mg/dL and in acute forms when intravenous calcium is necessary (40)(41)(42). Permanent hypoparathyroidism requires lifelong followup (43,44). Recently, daily PTH injections have been introduced in one 2 years study in order to reduce the necessary of calcium and vitamin D (45).…”
Section: General Datamentioning
confidence: 99%
“…The association of intraoperative or postoperative IPTH with hypocalcemia has been well described . The utility of IPTH gradient has also been explored, with optimal cut points for predicting hypocalcemia approximately 60% to 80% .…”
Section: Discussionmentioning
confidence: 99%